The relationship between sexual function and mental health in Iranian pregnant women during the COVID-19 pandemic - Fatemeh Effati-Daryani; Shayesteh Jahanfar; Azam Mohammadi; Somayeh Zarei; Mojgan Mirghafourvand (BMC, 2021)
Abstract Background Sexual function, a significant contributor to quality of life, is affected by various factors, including overall mental health. COVID-19 is a current pandemic that influences the mental health of various populations, especially pregnant women. Despite the importance of sexual health, the specific nature of its relationship to overall mental health during the COVID-19 pandemic is not clearly defined. Thus, this study investigates the relationship between sexual function and mental health during the COVID-19 pandemic in Iranian pregnant women. Methods This descriptive-analytical, cross-sectional study was carried out among 437 pregnant women using the sociodemographic and obstetrics characteristics questionnaire, Female Sexual Function Inventory, Stress, Depression, and Anxiety Scales. Random sampling was employed to select pregnant women who had a medical record in Health Centers of Tabriz city, Iran. The questionnaires were sent to the participants' cell phones via WhatsApp or text messages, including links of questionnaires and the participants completed these questionnaires. Spearman correlation test was used to determine the relationship between sexual function and stress, anxiety, and depression. Generalized linear modeling was used to estimate each of the independent variables (sociodemographic characteristics, stress, anxiety, and depression) on the dependent variable (sexual function). Results The mean (Standard Deviation) sexual functioning (total) score was 20.0 (8.50) from the available range of 2 to 36. The mean (SD) of depression, stress, and anxiety scale was 4.81 (5.22), 5.13 (4.37), and 7.86 (4.50) (possible score ranging from 0 to 21), respectively. Based on Spearman's correlation test, there was a significant reverse correlation between the total sexual function score and stress, anxiety, and depression, indicating that all three variables negatively impacted sexual functioning. Variables such as mild stress, spouse type of job, sufficient household income, living with parents, higher marital satisfaction, and higher gestational age had a significant, positive impact on sexual function and could predict 35.8% of the variance model. Conclusions Sexual functioning was significantly impacted by stress, anxiety, and depression - all of which are heightened during a pandemic. This topic warrants further study, and the general public should be educated on the protective influence of safe sex/intimacy on overall mental health.